Liver Fibrosis Scores and Hospitalization, Mechanical Ventilation, Severity, and Death in Patients with COVID-19: A Systematic Review and Dose-Response Meta-Analysis. (29th March 2022) - Liu, Menglu; Mei, Kaibo; Tan, Ziqi; Huang, Shan; Liu, Fuwei; Deng, Chao; Ma, Jianyong; Yu, Peng; Liu, Xiao
Abstract : Background and Aim . The relationship between liver fibrosis scores and clinical outcomes in patients with COVID-19 is not compressively assessed. Methods . We identified relevant cohort studies that assessed the relationship between liver fibrosis scores (e.g., FIB-4, NAFLD fibrosis score (NFS), and aspartate aminotransferase to platelet ratio index (APRI)) and associated prognosis outcomes by searching the PubMed, EMBASE, and medRxiv databases. The potential dose-response effect was performed using a stage robust error meta-regression. Results . Sixteen studies with 8, 736 hospitalized patients with COVID-19 were included. One-point score in FIB-4 increase was significantly associated with increased mechanical ventilation (RR: 2.23, 95% CI: 1.37–3.65, P = 0.001 ), severe COVID-19 (RR: 1.82, 95% CI: 1.53–2.16, P < 0.001 ), and death (RR: 1.47, 95% CI: 1.31–1.65, P < 0.001 ), rather than hospitalization (RR: 1.35, 95% CI: 0.72–2.56, P = 0.35 ). Furthermore, there is a significant positive linear relationship between FIB-4 and severe COVID-19 (P nonlinearity = 0.12 ) and mortality (P nonlinearity = 0.18 ). Regarding other liver scores, one unit elevation in APRI increased the risk of death by 178% (RR: 2.78, 95% CI: 1.10–6.99, P = 0.03 ). Higher NFS (≥−1.5) and Forns index were associated with increased risk of severe COVID-19 and COVID-19-associated death. Conclusion . Our dose-response meta-analysis suggests high liver fibrosis scores are associated with worse prognosis in patients with COVID-19. For patients with COVID-19 at admission, especially for those with coexisting chronic liver diseases, assessment of liver fibrosis scores might be useful for identifying high risk of developing severe COVID-19 cases and worse outcomes.